Slots of Power-Law Profile as Acoustic Black Holes for Flexural Waves in Metallic and Composite Plates. (May 2016) - Bowyer, E.P.; Krylov, V.V.
Abstract: A new method of damping flexural vibrations in plate-like structures based on the 'acoustic black hole effect' has been recently developed and investigated. As 'acoustic black holes', one-dimensional elastic wedges of power-law profile covered by narrow strips of absorbing layers near sharp edges have been used initially. The addition of such power-law profiled wedges to edges of rectangular plates or strips results in substantial increase in damping of resonant flexural vibrations in such plates or strips due to the more efficient absorption of flexural waves at the tips of power-law wedges. One of the problems faced by this method of damping is having the wedge tips exposed on the outer edges of the plate or strip. One of the solutions to this problem is to move the wedges inside a plate, so that they form edges of power-law slots within the plate. The present paper reports the results of the experimental investigations into the effects of such slots on damping flexural vibrations. The obtained experimental results show that introducing power-law profiled slots within plates represents an effective method of damping flexural vibrations, which is comparable with the method using power-law wedges at plate edges.